THE INFLUENCE OF CUSTOMER EXPERIENCE AND TRUST ON CUSTOMER LOYALTY IN PT. TELKOM INDONESIA INDIHOME PRODUCTS - Yolanda Veybitha; Muhni Pamuji; Frecilia Nanda Melvani; Sari Sakarina; Kusminaini Armin; Yoga Abdy Baihaqi (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2025)
IndiHome is a home internet service from Telkomsel that provides internet connection, landline telephone, and interactive TV (IPTV) in one package. Previously owned by PT Telkom Indonesia, IndiHome is now managed by Telkomsel. IndiHome offers a variety of package options with different internet speeds, as well as additional services such as wifi.id seamless and others. This study aims to measure the influence of customer experience and trust variables on customer loyalty. The population in this study was Indihome customers in the city of Palembang in 2024 as many as 11,883, while the sample taken was 99 respondents. This study is quantitative, data was obtained by distributing questionnaires and processed using the SPSS program. The results of the study showed that customer experience and trust variables have a significant effect both simultaneously and partially on customer loyalty. For future research, external variables can be included and the research model can be modified by using mediating variables.